Law Enforcement Against Vehicle Theft Perpetrators Using the Modus of Destruction and Selling Evidence - Zidan Naufal Syailendra; Arpangi Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This study aims to analyze the implementation of law enforcement against perpetrators of motor vehicle theft using the modus operandi of damaging and selling evidence, identify the obstacles faced by law enforcement officers in the process of proof and prosecution, and formulate optimal strategies based on the integration of substantive law analysis, procedural law analysis, and the Islamic legal perspective. The case of District Court Decision No. 44/Pid.B/2025/PN Bgr serves as the primary case study to examine the application of Article 363 paragraph (1) points 4 and 5 of the Indonesian Criminal Code (KUHP) in judicial practice and its implications for the effectiveness of law enforcement. This research employs a normative juridical approach combined with a case approach and a statutory approach. Data were obtained from court decisions, relevant legislation, academic literature, and previous related research. The analysis was conducted qualitatively by synthesizing normative and empirical findings to assess the consistency of legal norm implementation as well as technical-forensic and institutional barriers in handling such cases. The findings indicate that the elements of Article 363 paragraph (1) points 4 and 5 of the Criminal Code are fulfilled when the act is committed jointly and by means of damage, as reflected in the Bogor District Court’s decision, which imposed imprisonment and ordered the return of evidence. However, the effectiveness of law enforcement remains hindered by several factors, including the alteration of evidence (commercialization of spare parts), weak supervision of second-hand markets, limited forensic capacity, and a lack of inter-agency data integration. To overcome these obstacles, it is necessary to strengthen forensic capacity, develop an integrated national database of vehicles and spare parts, regulate second-hand markets and prosecute receivers of stolen goods, and integrate Islamic legal values into penal policy emphasizing rehabilitation and prevention.